Overexpression of Multifunctional Protein p32 Promotes a Malignant Phenotype in Colorectal Cancer Cells - Egusquiza-Alvarez, Carlos Alejandro; Castañeda-Patlán, M. Cristina; Albarran-Gutierrez, Sara; Gonzalez-Aguilar, Héctor; Moreno-Londoño, Angela P.; Maldonado, Vilma; Melendez-Zajgla, Jorge; Robles-Flores, Martha (Frontiers in Oncology, 2021)
p32 is a multifunctional and multicompartmental protein that has been found upregulated in numerous adenocarcinomas, including colorectal malignancy. High levels of p32 expression have been correlated with poor prognosis in colorectal cancer. However, the functions performed by p32 in colorectal cancer have not been characterized. Here we show that p32 is overexpressed in colorectal cancer cell lines compared to non-malignant colon cells. Colon cancer cells also display higher nuclear levels of p32 than nuclear levels found in non-malignant cells. Moreover, we demonstrate that p32 regulates the expression levels of genes tightly related to malignant phenotypes such as HAS-2 and PDCD4. Remarkably, we demonstrate that knockdown of p32 negatively affects Akt/mTOR signaling activation, inhibits the migration ability of colon malignant cells, and sensitizes them to cell death induced by oxidative stress and chemotherapeutic agents, but not to cell death induced by nutritional stress. In addition, knockdown of p32 significantly decreased clonogenic capacity and in vivo tumorigenesis in a xenograft mice model. Altogether, our results demonstrate that p32 is an important promoter of malignant phenotype in colorectal cancer cells, suggesting that it could be used as a therapeutic target in colorectal cancer treatment.